2015
DOI: 10.1038/srep09568
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into ductile fracture of ultrafine-grained Al-Mg alloys

Abstract: It is well known that when coarse-grained metals undergo severe plastic deformation to be transformed into nano-grained metals, their ductility is reduced. However, there are no ductile fracture criteria developed based on grain refinement. In this paper, we propose a new relationship between ductile fracture and grain refinement during deformation, considering factors besides void nucleation and growth. Ultrafine-grained Al-Mg alloy sheets were fabricated using different rolling techniques at room and cryogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…[11][12][13] Variants of the SPD techniques such as asymmetric cryorolling, [14,15] Accumulative Roll Bonding (ARB) [16,17] and Asymmetric Rolling (AR) [18,19] have been developed to enable bulk fabrication of nanostructured/ultrafine-grained metal sheets/foils. The ARB and AR techniques can be used to produce continuous products and are more feasible for practical application in industries.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Variants of the SPD techniques such as asymmetric cryorolling, [14,15] Accumulative Roll Bonding (ARB) [16,17] and Asymmetric Rolling (AR) [18,19] have been developed to enable bulk fabrication of nanostructured/ultrafine-grained metal sheets/foils. The ARB and AR techniques can be used to produce continuous products and are more feasible for practical application in industries.…”
Section: Introductionmentioning
confidence: 99%
“…This matches well with the value reported by Wen et al, [32] who found that coarse copper powders attained an ultimate stable grain size of ~100 nm during HPT at room temperature. For UFG AA5052 sheets, Yu et al [22] investigated the grain distribution at the fracture surface and proposed a relationship between ductile fracture and grain refinement during deformation besides the void nuclear and growth. As the grains are refined to a nano size approaching the theoretical minimum achievable value, the material becomes brittle in the shear band zone.…”
Section: Mompiou Et Almentioning
confidence: 99%
“…Recently, Yu et al [81][82][83][84] combined the features of AR and CR to fabricate UFG/NG metals. A schematic illustration of ACR is shown in Fig.…”
Section: Asymmetric Cryorolling (Acr)mentioning
confidence: 99%
“…The ACR technique has been used successfully to produce UFG Al 1050, [81] 6061 [82][83] and 5052 [84] alloys. Following ACR, the grain size in Al 1050 sheet with the roll speed ratio (RRS) 1.4 is seen to be much finer than that with the RRS 1.1.…”
Section: Asymmetric Cryorolling (Acr)mentioning
confidence: 99%
See 1 more Smart Citation